1970
DOI: 10.1039/c29700000897
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the lythraceae alkaloids: mode of incorporation of phenylalanine

Abstract: Two fragments derived from phenylalanine (l), one a c&3 unit, the other probably a c& unit, are incorporated into the Lythraceae alkaloid, decodine (2).ACTIVITY from @14C]phenylalanine (1) enters the two predicted positions (0) of the phenylquinolizidine alkaloid cryogeninel [an isomer of 0-methyl-1 ',2'-dehydro-(2) J This observation was consistent with the four hypothe~es~l-~ summarized in ref. 4, which have been advanced to account for the origin of this group of alkaloids, but did not distinguish among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The relative configuration of C-5 was confirmed using its ROESY correlation. H-1 and H-3, being axially and equatorially oriented on biogenetic considerations, , respectively, were used as the basis for correlations. H-1, at δ H 4.00, showed ROESY cross-peaks with H-2eq, H-6ax, and H-8ax, while there was no detectable interaction between H-1 and H-5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative configuration of C-5 was confirmed using its ROESY correlation. H-1 and H-3, being axially and equatorially oriented on biogenetic considerations, , respectively, were used as the basis for correlations. H-1, at δ H 4.00, showed ROESY cross-peaks with H-2eq, H-6ax, and H-8ax, while there was no detectable interaction between H-1 and H-5.…”
mentioning
confidence: 99%
“…This proton showed a ROESY correlation with H-1 (δ H 2.99) along with H-7ax (δ H 1.14) and H-9ax (δ H 1.21) (Figure 2), indicating a trans-fused quinolizidine ring system. Considering the configuration of C-1 and C-3, 14,15 the structure of compound 2 can be elucidated as dihydrolyfoline (2). The minimum energy conformation of 2 and key ROESY correlations are shown in Figure 2.…”
mentioning
confidence: 99%
“…C-13 and at no other site, with a distribution such that the ratios of activities, C-3/C-1, and C-1 l/C-13, each equalled the ratio of activities -C02H/P-CH2 within the doubly labelled phenylalanine serving as their precursor. This was indeed ~b s e r v e d :~ each of the four pre-4A different result of this experiment was recorded in a preliminary communication (30). It was reported that the hemipinic anhydride obtained by degradation of decodine derived from the experiment with [1,phenylalanine (now referred to as experiment 12) accounted for 46% of the activity of the alkaloid.…”
Section: (1)mentioning
confidence: 98%